The inﬂuence of computer on examining trigonometric functions - Takači, Djurdjica; Stojković, Radivoje; Radovanović, Jasminka (Teaching Mathematics and Computer Science, 2008)
In this paper the influence of computer on examining trigonometric functions was analyzed throughout the results questionnaire. The students, as usual, had to examine two trigonometric functions, both were given with the appropriate instructions. Three groups were tested. Two of those three groups were prepared with the help of computer and the third one was taught without computer. From the analysis of the questionnaire it follows that the computer has a great influence on understanding of the connections between the graph and very complex calculations.